2007
DOI: 10.3390/ijerph2007040007
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-L-Cysteine Affords Protection against Lead-Induced Cytotoxicity and Oxidative Stress in Human Liver Carcinoma (HepG2) Cells

Abstract: Although lead exposure has declined in recent years as a result of change to lead-free gasoline, several epidemiological have pointed out that it represents a medical and public health emergency, especially in young children consuming high amounts of lead-contaminated flake paints. A previous study in our laboratory indicated that lead exposure induces cytotoxicity in human liver carcinoma cells. In the present study, we evaluated the role of oxidative stress in lead-induced toxicity, and the protective effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 29 publications
4
45
0
Order By: Relevance
“…These findings showed a clear evidence that NAC acts as a potential chelator that attenuates ATO toxicity in HL-60 cells ( Fig 5). This study is consistent with a recent in vitro finding from our laboratory indicating that NAC affords cellular protection against lead-induced cytotoxicity and oxidative stress in human liver carcinoma (HepG2) cells [29]. Further, previous studies have demonstrated that NAC has potential as an anti-tumorigenic agent with efficacy in preventing initial tumor take and metastasis [30,31].…”
Section: N-acetyl-l-cysteine Inhibits the Cytotoxicity Of Arsenic Trisupporting
confidence: 92%
“…These findings showed a clear evidence that NAC acts as a potential chelator that attenuates ATO toxicity in HL-60 cells ( Fig 5). This study is consistent with a recent in vitro finding from our laboratory indicating that NAC affords cellular protection against lead-induced cytotoxicity and oxidative stress in human liver carcinoma (HepG2) cells [29]. Further, previous studies have demonstrated that NAC has potential as an anti-tumorigenic agent with efficacy in preventing initial tumor take and metastasis [30,31].…”
Section: N-acetyl-l-cysteine Inhibits the Cytotoxicity Of Arsenic Trisupporting
confidence: 92%
“…However, poor data demonstrate the ability of H 2 O 2 and NAC to exert their pro-and anti-oxidant action in hepatoma cell lines. Furthermore, the window within which H 2 O 2 and NAC are capable to promote/inhibit both apoptosis and cell proliferation in this in vitro model of hepatic cells is still unknown (28)(29)(30).…”
Section: Proliferative and Apoptotic Response Was Dose-related In Hepmentioning
confidence: 97%
“…Previous findings show that supplementation of Acanthopanax sessiliflorus extract exhibits an increased resistance to heat stress and UV irradiation in C. elegans (Park et al, 2014). N-acetyl-L-cysteine, a sulfur-containing cysteine derivative with an acetyl group attached to the nitrogen of cysteine, has anti-oxidant and anti-cancer activity (Cai et al, 1999;Yedjou & Tchounwou, 2007). Survival of worms after heat shock or UV irradiation significantly increases by pre-treatment with 5 mM N-acetyl-L-cysteine (Dh et al, 2015).…”
Section: Effect Of a Annua On Response To Heat Shock And Uv Irradiationmentioning
confidence: 99%